2020
DOI: 10.1371/journal.pone.0233175
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate positive feedback facilitates sense of agency and performance for a reaching movement task with a virtual hand

Abstract: This study investigated the generalized effects of positive feedback (PF) versus negative feedback (NF) during training on performance and sense of agency for a reach-to-touch task with a virtual hand. Virtual reality (VR) is increasingly employed for rehabilitation after neuromuscular traumas such as stroke and spinal cord injury. However, VR methods still need to be optimized for greater effectiveness and engagement to increase rates of clinical retention. In this study, we observed that training with dispro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Improved motor control may be enacted from training the person to move better independently or with the assistance of a powered device. Regardless of the rehabilitation approach, the person should be cognitively engaged and integrated with the therapeutic platform or the assistive device ( Moore and Fletcher, 2012 ; Nataraj, 2017 ; Nataraj et al, 2020a , b , c ). Improved perception of involvement and control of movement should better ensure continued participation and positive functional outcomes ( Doyle, 2002 ; Behrman et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved motor control may be enacted from training the person to move better independently or with the assistance of a powered device. Regardless of the rehabilitation approach, the person should be cognitively engaged and integrated with the therapeutic platform or the assistive device ( Moore and Fletcher, 2012 ; Nataraj, 2017 ; Nataraj et al, 2020a , b , c ). Improved perception of involvement and control of movement should better ensure continued participation and positive functional outcomes ( Doyle, 2002 ; Behrman et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agency is naturally implicated with rehabilitation through perception of neuromuscular action and related functional consequences ( Moore and Obhi, 2012 ). Agency contributes to the performance of functional movements such as reaching ( Nataraj et al, 2020c , d ) and is impaired in the presence of neurological disorders ( Jeannerod, 2009 ; Ritterband-Rosenbaum et al, 2012 ). Agency can also be compromised during the use of powered assistive devices, such as exoskeletons ( Hartigan et al, 2015 ) or sensorimotor prostheses ( Antfolk et al, 2013 ; Hebert et al, 2013 ), due to distortions in embodiment ( Kilteni et al, 2012 ; Caspar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such judgment may also be influenced by higher level factors such as intentions, beliefs, and inferences, besides lower levels of feeling of control 51 . Visually improved task-performance feedback can boost the rating of agency [52][53][54] . The positive taskperformance feedback probably also contributed to the enhanced sense of agency.…”
Section: Discussionmentioning
confidence: 99%
“…For intentional binding, the evidence for affect-specific influences is mixed. Some studies found that negative compared to neutral or positive action outcomes decrease temporal binding (Takahata et al, 2012 ; Yoshie and Haggard, 2013 ; Barlas and Obhi, 2014 ; Borhani et al, 2017 ; Haggard, 2017 ; Nataraj et al, 2020 ). Since less temporal binding is assumed to indicate lower sense of agency, these findings are consistent with studies employing explicit agency measures, which found that negative action outcomes were associated with lower sense of agency.…”
Section: Does Affect Influence Sense Of Agency?mentioning
confidence: 99%
“…Outcome agency : Since our actions are usually aimed at producing specific effects, such as obtaining rewards, we are more likely to feel in control when we can reliably produce the desired outcome (Moscarello and Hartley, 2017 ; Ly et al, 2019 ). Accordingly, some experiments manipulate agency experience by ensuring either that it is possible to produce a positive outcome (e.g., via highly reliable action-effect contingencies; high outcome agency), or giving participants no reliable chance to achieve the desired outcome (e.g., via random action-effect contingencies, low outcome agency; e.g., Nataraj et al, 2020 ; Li et al, 2021 ). Agency here means the ability to influence the environment in a way which is desirable to the agent.…”
Section: Does Sense Of Agency Influence Affective Processing?mentioning
confidence: 99%